IMPLEMENTASI MANAJEMEN KEPEMIMPINAN MENINGKATKAN MUTU PENDIDIKAN DAN EFEKTIVITAS ORGANISASI SEKOLAH DI SMA NEGERI 2 METRO - Solehan; Ali Kurniawan (CV JK Riset Publishing Group, 2025)
This study analyzes the implementation of leadership management at SMA Negeri 2 Metro in improving education quality and school organizational effectiveness. Using a qualitative approach with case study design, data were collected through in-depth interviews, participatory observation, and documentation study involving principals, vice principals, teachers, and educational staff. Results indicate that principals implement transformational leadership through visionary strategies, continuous teacher empowerment, collaborative culture, curriculum innovation, data-based monitoring, distributive leadership, and digital technology integration. This implementation resulted in fifteen percent increase in student academic achievement, teacher job satisfaction of four point three on a five-point scale, and formation of productive professional learning communities. The study constructs an Ecosystemic-Transformative Leadership Model integrating five fundamental dimensions in Indonesian education context. This model emphasizes leadership as an ecological phenomenon influencing the entire school ecosystem through various interconnected pathways of influence to achieve sustainable organizational transformation.